Converting Industrial Cold Pressed Avocado Oil Waste into Higher Value Products - Permal, Rahul Kaushik (Auckland University of Technology, 2022)
Organic cold-pressed avocado oil (CPAO) has seen a steady incline in popularity over the past years due to its health promoting benefits and versatile culinary applications. However, the CPAO extraction process is relatively inefficient because of large amounts of by-product and organic wastes generated. To put this into perspective, for every 100 kg of avocado oil extracted; 570 kg of avocado wastewater (AWW), 350 kg of avocado skin and seeds and 190 kg of avocado pomace are generated. At present the pomace is utilised as animal feed but the skin, seed and wastewater are discarded into landfill. This disposal practice is of great concern as it causes pollution to the New Zealand environment and incurs high disposal costs to the avocado oil industry. A small body of studies have explored ways to utilise the avocado skin and seed. However, no research has been conducted on the use and application of AWW. Hence the aim of this study is to convert avocado skin, seed and wastewater into value added products. The success of this research would aid waste management in the avocado industry, as well as alleviate environmental impact from waste disposal and potentially create an avenue to generate additional income for the avocado oil industry. Proximate analysis and antioxidant analysis of CPAO by-products were conducted. The largest by-product, AWW was successfully spray dried into powder using various temperatures ranging from 110˚C to 160˚C. The powders were then utilised as preservatives in pork sausages to prevent lipid oxidation. While exploring for potential application of AWW powder, spray drying parameters were adjusted to increase yield of AWW powder with the addition of carriers and encapsulation techniques. AWW encapsulated with 5% whey protein isolate was then tested as a preservative in cooked pork fat. Findings showed that the effectiveness of AWW powder in preventing lipid oxidation was comparable to commercial preservatives. 2 Avocado seeds which account for approximately 13% of the by-products from industrial CPAO extraction was converted into an extruded snack using a friction cooker. Potential toxins such as amygdalin and persin were quantified in the seed snack. Both toxins were found in low concentrations would not have a negative impact on the human body if the snack was friction cooked and then consumed. Overall, this thesis demonstrated the use of various modern technologies such as friction cooking, encapsulation, and spray drying to valorise the avocado by-products. Classical and current analytical techniques were also used in conjunction to the above technologies to provide an insight into various ways that CPAO by-products could be upcycled.